MEDICAL CLERKSHIPS' PERCEPTION AND FACTORS IN ACQUISITION OF KNOWLEDGE AND SKILLS DURING COVID-19 PANDEMIC - Oscar Gilang Purnajati; Fransisca Galuh Widowati; Haryo Dimasto Kristianto (Berkala Ilmiah Kedokteran Duta Wacana, 2022)
Background The global COVID-19 pandemic has changed Medical Education in general. Many changing policies are a challenge, and we must evaluate the results. Medical clerkship program presents a challenge of its own. Delay in rotation time, work restrictions, and reduced contact with patients can cause a lack of accuracy and realism in integrating knowledge and skills that should be the outcome of this clerkship.Objective We need to explore the impact of COVID-19 pandemic in clinical rotation in general perception and the factors that influence the acquisition of knowledge and skills in medical clerkship education.Method A qualitative study by comparing 2 groups, before pandemic and during pandemic group and explores the factors that influence the acquisition of knowledge and skills through focus group discussions (FGD).Results Conclusion The general perception obtained in this study included workload and knowledge acquisition, and the specific factors that influenced the acquisition of knowledge and skills were the existence of role models, feedback, and teaching and learning models during the pandemic.Conclusion The COVID-19 pandemic did not significantly affect knowledge acquisition of medical clerkship, but it had some effect on skill acquisition. Specific factors that influenced medical clerkship learning during this pandemic were role modelling and teaching-learning because of reduced face-to-face session between the clinical supervisors and the student. The feedback factor was almost not affected.